2019
DOI: 10.2147/copd.s214389
|View full text |Cite
|
Sign up to set email alerts
|

<p>A survey exploring knowledge and beliefs about electronic cigarettes between health care providers and the general population in Egypt</p>

Abstract: Background: Electronic cigarettes are increasing in popularity, and they are easily accessible in a variety of locations. Despite increasing its popularity, little is known about its overall health effects. Physicians have rated the most trustful source of information about it and play also a role in disseminating information about it. Thus, this study identified the difference in knowledge and beliefs about electronic cigarettes between health care providers and the general population in Egypt. Methods: A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…Several published studies have been conducted to evaluate the beliefs and attitudes toward E-cig [30][31][32][33]. In contrary to our results, in Dwedar et al's study [30], most health care providers believed that E-cig was unsafe and did not help in smoking cessation, while Tamimi's study [31] reported that many E-cig users approached it as a therapeutic aid to stop or cut down tobacco smoking, despite that some of the participants used E-cig as a hobby and a social activity [31]. These contradictions in results between these studies and our study might be attributed to the different target population that has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies have been conducted to evaluate the beliefs and attitudes toward E-cig [30][31][32][33]. In contrary to our results, in Dwedar et al's study [30], most health care providers believed that E-cig was unsafe and did not help in smoking cessation, while Tamimi's study [31] reported that many E-cig users approached it as a therapeutic aid to stop or cut down tobacco smoking, despite that some of the participants used E-cig as a hobby and a social activity [31]. These contradictions in results between these studies and our study might be attributed to the different target population that has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Section C comprised a 7-item Generalized Anxiety Disorder (GAD-7) scale (range, 0-21), which assessed self-reported symptoms and severity of anxiety respectively. The total scores of GAD-7 were categorized as normal (0-5), mild (6)(7)(8)(9)(10), moderate to severe (�11) anxiety. The GAD scale has been validated in Nigeria using a large and diverse sample of the population [19].…”
Section: Data Collection Toolmentioning
confidence: 99%
“…In Africa, to our knowledge, few studies have explored the use of e-cigarettes. On the continent, knowledge levels of between 57% and 79% have been reported [9,10], with a majority of ever users between ages 21-30 years, and a self-reported history of use not exceeding 12 months [11]. Other studies have also detailed the potentially deleterious effect of e-cigarette use in depressing long-term cessation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found in a study conducted in Jordan, which showed that e-cig users agreed that using an e-cig is safer than tobacco smoking to both the user and surroundings, and that it is cheaper and can help in smoking cessation [4]. On the other hand, the literature suggests that high use of e-cigs is not medically recommended as most healthcare providers believe that e-cigs are unsafe and do not help with tobacco smoking cessation [26].…”
Section: Domain N (%)mentioning
confidence: 99%